Difference between revisions of "009A Sample Final 1, Problem 3"

From Math Wiki
Jump to navigation Jump to search
(Created page with "<span class="exam">Find the derivatives of the following functions. <span class="exam">a) <math style="vertical-align: -16px">f(x)=\ln \bigg(\frac{x^2-1}{x^2+1}\bigg)</math>...")
 
 
(2 intermediate revisions by the same user not shown)
Line 1: Line 1:
 
<span class="exam">Find the derivatives of the following functions.
 
<span class="exam">Find the derivatives of the following functions.
  
<span class="exam">a) <math style="vertical-align: -16px">f(x)=\ln \bigg(\frac{x^2-1}{x^2+1}\bigg)</math>
+
<span class="exam">(a) &nbsp; <math style="vertical-align: -14px">f(x)=\ln \bigg(\frac{x^2-1}{x^2+1}\bigg)</math>
  
<span class="exam">b) <math style="vertical-align: -5px">g(x)=2\sin (4x)+4\tan (\sqrt{1+x^3})</math>
+
<span class="exam">(b) &nbsp; <math style="vertical-align: -3px">g(x)=2\sin (4x)+4\tan (\sqrt{1+x^3})</math>
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Foundations: &nbsp;  
 
!Foundations: &nbsp;  
 
|-
 
|-
|For functions <math style="vertical-align: -5px">f(x)</math>&thinsp; and <math style="vertical-align: -5px">g(x)</math>, recall
+
|'''1.''' '''Chain Rule'''
 
|-
 
|-
|&nbsp;
+
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\frac{d}{dx}(f(g(x)))=f'(g(x))g'(x)</math>
 
|-
 
|-
|'''Chain Rule:'''&nbsp; <math>\frac{d}{dx}(f(g(x)))=f'(g(x))g'(x)</math>
+
|'''2.''' '''Quotient Rule'''
 
|-
 
|-
|&nbsp;
+
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\frac{d}{dx}\bigg(\frac{f(x)}{g(x)}\bigg)=\frac{g(x)f'(x)-f(x)g'(x)}{(g(x))^2}</math>
 
|-
 
|-
|'''Quotient Rule:'''&nbsp; <math>\frac{d}{dx}\bigg(\frac{f(x)}{g(x)}\bigg)=\frac{g(x)f'(x)-f(x)g'(x)}{(g(x))^2}</math>
+
|'''3.''' '''Trig Derivatives'''
 
|-
 
|-
|&nbsp;
+
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\frac{d}{dx}(\sin x)=\cos x,\quad\frac{d}{dx}(\tan x)=\sec^2 x</math>
|-
 
|'''Trig Derivatives:'''&nbsp; <math>\frac{d}{dx}(\sin x)=\cos x,\quad\frac{d}{dx}(\tan x)=\sec^2 x</math>
 
|-
 
|&nbsp;
 
 
|}
 
|}
 +
  
 
'''Solution:'''
 
'''Solution:'''
Line 34: Line 31:
 
|Using the Chain Rule, we have
 
|Using the Chain Rule, we have
 
|-
 
|-
|<br>
+
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
 
\displaystyle{f'(x)} & = & \displaystyle{\frac{1}{\bigg(\frac{x^2-1}{x^2+1}\bigg)}\bigg(\frac{d}{dx}\bigg(\frac{x^2-1}{x^2+1}\bigg)\bigg)}\\
 
\displaystyle{f'(x)} & = & \displaystyle{\frac{1}{\bigg(\frac{x^2-1}{x^2+1}\bigg)}\bigg(\frac{d}{dx}\bigg(\frac{x^2-1}{x^2+1}\bigg)\bigg)}\\
 
&&\\
 
&&\\
Line 45: Line 42:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|Now, we need to calculate &thinsp;<math>\bigg(\frac{d}{dx}\bigg(\frac{x^2-1}{x^2+1}\bigg)\bigg).</math>
+
|Now, we need to calculate &nbsp;<math>\bigg(\frac{d}{dx}\bigg(\frac{x^2-1}{x^2+1}\bigg)\bigg).</math>
 
|-
 
|-
 
|To do this, we use the Quotient Rule. So, we have
 
|To do this, we use the Quotient Rule. So, we have
 
|-
 
|-
|<br>
+
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
 
\displaystyle{f'(x)} & = & \displaystyle{\frac{x^2+1}{x^2-1}\bigg(\frac{d}{dx}\bigg(\frac{x^2-1}{x^2+1}\bigg)\bigg)}\\
 
\displaystyle{f'(x)} & = & \displaystyle{\frac{x^2+1}{x^2-1}\bigg(\frac{d}{dx}\bigg(\frac{x^2-1}{x^2+1}\bigg)\bigg)}\\
 
&&\\
 
&&\\
Line 68: Line 65:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|Again, we need to use the Chain Rule. We have
+
|We need to use the Chain Rule. We have
 
|-
 
|-
 
|
 
|
::<math>g'(x)\,=\,8\cos(4x)+4\sec^2(\sqrt{1+x^3})\bigg(\frac{d}{dx}\sqrt{1+x^3}\bigg).</math>
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>g'(x)\,=\,8\cos(4x)+4\sec^2(\sqrt{1+x^3})\bigg(\frac{d}{dx}\sqrt{1+x^3}\bigg).</math>
 
|}
 
|}
  
Line 77: Line 74:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|We need to calculate&thinsp; <math>\frac{d}{dx}\sqrt{1+x^3}.</math>
+
|We need to calculate &nbsp; <math>\frac{d}{dx}\sqrt{1+x^3}.</math>
 
|-
 
|-
 
|We use the Chain Rule again to get
 
|We use the Chain Rule again to get
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{g'(x)} & = & \displaystyle{8\cos(4x)+4\sec^2(\sqrt{1+x^3})\bigg(\frac{d}{dx}\sqrt{1+x^3}\bigg)}\\
 
\displaystyle{g'(x)} & = & \displaystyle{8\cos(4x)+4\sec^2(\sqrt{1+x^3})\bigg(\frac{d}{dx}\sqrt{1+x^3}\bigg)}\\
 
&&\\
 
&&\\
Line 90: Line 87:
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
 +
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;  
 
!Final Answer: &nbsp;  
 
|-
 
|-
|'''(a)''' <math style="vertical-align: -14px">f'(x)=\frac{4x}{x^4-1}</math>
+
|&nbsp; &nbsp; '''(a)''' &nbsp; &nbsp; <math style="vertical-align: -14px">f'(x)=\frac{4x}{x^4-1}</math>
 
|-
 
|-
|'''(b)''' <math style="vertical-align: -18px">g'(x)=8\cos(4x)+\frac{6\sec^2(\sqrt{1+x^3})x^2}{\sqrt{1+x^3}}</math>
+
|&nbsp; &nbsp; '''(b)''' &nbsp; &nbsp; <math style="vertical-align: -18px">g'(x)=8\cos(4x)+\frac{6\sec^2(\sqrt{1+x^3})x^2}{\sqrt{1+x^3}}</math>
 
|}
 
|}
 
[[009A_Sample_Final_1|'''<u>Return to Sample Exam</u>''']]
 
[[009A_Sample_Final_1|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 08:08, 10 April 2017

Find the derivatives of the following functions.

(a)  

(b)  

Foundations:  
1. Chain Rule
       
2. Quotient Rule
       
3. Trig Derivatives
       


Solution:

(a)

Step 1:  
Using the Chain Rule, we have

       

Step 2:  
Now, we need to calculate  
To do this, we use the Quotient Rule. So, we have

       

(b)

Step 1:  
We need to use the Chain Rule. We have

       

Step 2:  
We need to calculate  
We use the Chain Rule again to get

       


Final Answer:  
    (a)    
    (b)    

Return to Sample Exam